(untitled) (TEST Ticontre. Theory Text Translation, 2023)
The aim of this essay is to read Bernari’s Tre operai (1934) through an analysis at the same time thematic and formal able to highlight not only the representational modalities through which the novel interprets and re-elaborates the images of incipient modernity, but also the technical-stylistic expedients capable of triggering a dialectical tension between the narrative system and the significant manifestations of the reality. The exegetical commitment underlying the examination of the novel also allows to re-evaluate a category with vague and excessively nuanced contours such as that of “neorealism”, especially when applied to the literary panorama of the Thirties, making it interact with more recent critical-theoretical concepts, such as that of “modernist realism”. In this way it is possible to question certain limiting critical hypothecs, especially moved by the Marxist criticism of the Sixties, and to reopen an interpretative discourse aimed at deepening the interactions between realistic models, expressionist distortions and modernist modules that found and substantiate the reasons for the text. Alla base di questa proposta vi è il tentativo di rileggere Tre operai di Bernari (1934) attraverso un’analisi al contempo tematica e formale in grado di evidenziare e porre in rilievo non solo le modalità rappresentative mediante cui il romanzo interpreta e rielabora gli iconemi della modernità incipiente, ma altresì gli espedienti tecnico-stilistici capaci di innescare una tensione dialettica tra l’impianto narrativo e le manifestazioni significanti della realtà raccontata. L’impegno esegetico sotteso all’esame del romanzo permette, inoltre, di rivalutare una categoria dai contorni vaghi ed eccessivamente sfumati come quella di “neorealismo”, soprattutto quando applicata al panorama letterario degli anni Trenta, facendola interagire con concetti critico-teorici più recenti, come quello di “realismo modernista”. In tal modo è possibile porre in questione certe ipoteche critiche limitanti, mosse specialmente dalla critica marxista degli anni Sessanta, e riaprire un discorso interpretativo atto ad approfondire le interazioni tra modelli realistici, distorsioni espressioniste e moduli modernisti che fondano e sostanziano le ragioni del testo.